Enhancing play environments for autistic children in special education schools: insights from the Yang Tze River Delta Region / Chen Jingjing and Alice Sabrina Ismail - Jingjing, Chen; Ismail, Alice Sabrina (Universiti Teknologi MARA, Perak, 2025)
This study explores the optimization of spatial and play environments for autistic children in special education schools within the Yangtze River Delta Region of China. Using a combination of the Mosaic Approach and case studies, the research investigated the sensory, cognitive, and social needs of autistic children, focusing on how specific design elements can support their development. Key findings highlight the importance of zoning, layout, sensory-friendly features, and interactive elements in creating effective play environments. The study emphasizes the need for a holistic design approach that integrates these elements to enhance the well-being and engagement of autistic children. Recommendations for policymakers, designers, and educators underscore the significance of collaborative efforts in designing inclusive educational spaces that cater to the unique needs of autistic children.